Performance and mechanism of removal of antibiotics and antibiotic resistance genes from wastewater by electrochemical carbon nanotube membranes - Wang, Jun; Liu, Hong; Chen, Xiaofei; Li, Ye; Sha, Xueni; Song, Huanjie; Li, Bolin; Yan, Zheng; Chang, Ming (Frontiers in Chemistry, 2022)
Electrochemical carbon nanotube (CNT) and carboxylated carbon nanotube (CNT-COOH) membranes were prepared by vacuum filtration for the removal of antibiotics and antibiotic resistance genes (ARGs) from water. Scanning electron microscopy and energy-dispersive spectroscopy were used to analyze the performances of the two electrochemical membranes in the removal of antibiotics and ARGs, to determine the effects of different factors on removal rates, and to explore the mechanisms of the removal of antibiotics and ARGs. The results showed that CNT-COOH formed a porous mesh structure on the surface of polytetrafluoroethylene membrane and contained more oxygen than CNT. The electrochemical CNT-COOH membrane showed higher antibiotic and ARG removal rates than the electrochemical CNT membrane, with an antibiotics removal rate of 82% after 60 min of reaction and an ARGs concentration decrease by 1.85 log. The removal rate of antibiotics and ARGs increased with the increase in electrolyte concentration and anode voltage but decreased with the increase in the influent flow rate. The removal rate of antibiotics decreased with the increase in pH, while the best removal rates of ARGs were observed in a neutral environment. The degradation mechanism of antibiotics on the electrochemical CNT-COOH membrane was analyzed, and possible antibiotic degradation pathways were proposed. The removal of antibiotics and ARGs mainly occurred through electrochemical degradation, where hydroxyl radicals (-OH) played a dominant role.